2005
DOI: 10.1080/17415990500151472
|View full text |Cite
|
Sign up to set email alerts
|

Addition of alkyllithiums to 3H-quinazoline-4-thione and various substituted quinazoline derivatives; application in synthesis

Abstract: Reaction of 3H-quinazoline-4-thione (1) with two mole equivalents of an alkyllithium (t-BuLi, n-BuLi or MeLi) at -78 C in dry THF gave the corresponding 2-alkyl-1,2-dihydro-3H-quinazoline-4-thione (4, 5 or 6) in high yield. Similarly, reactions of 4-(methylthio)quinazoline (7), 4-(ethylthio)quinazoline (8) and 4-methoxyquinazoline (9) with alkyllithiums (one mole equivalent) gave the corresponding 4-substitued 2-alkyl-1,2-dihydroquinazolines 11-18. On the other hand, blocking position 2 with a phenyl group in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…149 The authors suggested that the reason for this difference could be due to the thiolate anion in 344 being less effective at donating negative charge to the ring than its oxygen counterpart. The acquisition of negative charge by the ring would be expected to deactivate the ring towards nucleophilic attack by alkyllithiums.…”
Section: Addition Of Alkyllithiums To 3h-quinazolin-4-thionesmentioning
confidence: 99%
See 4 more Smart Citations
“…149 The authors suggested that the reason for this difference could be due to the thiolate anion in 344 being less effective at donating negative charge to the ring than its oxygen counterpart. The acquisition of negative charge by the ring would be expected to deactivate the ring towards nucleophilic attack by alkyllithiums.…”
Section: Addition Of Alkyllithiums To 3h-quinazolin-4-thionesmentioning
confidence: 99%
“…149 Compound 358 was the very product that might have been expected from the reaction of 3H-quinazolin-4-one with t-BuLi, but, of course, this direct reaction of 3H-quinazolin-4-one with t-BuLi did not occur. 149 Compound 358 was obtained due to nucleophilic addition of t-BuLi at the 2-position of 105 followed by a C=O formation at the 4-position. Yield of isolated product after column chromatography.…”
Section: Addition Of Alkyllithiums To Substituted Quinazolinesmentioning
confidence: 99%
See 3 more Smart Citations